Clinical significance and immunobiology of IL-21 in autoimmunity. (May 2019) - Long, Di; Chen, Yongjian; Wu, Haijing; Zhao, Ming; Lu, Qianjin
Abstract: Interleukin-21 (IL-21), an autocrine cytokine predominantly produced by follicular helper T (Tfh) and T helper 17 (Th17) cells, has been proven to play an important role in the immune system, for example, by promoting proliferation and the development of Tfh and Th17 cells, balancing helper T cell subsets, inducing B cell generation and differentiation into plasma cells, and enhancing the production of immunoglobulin. These effects are mainly mediated by activation of the JAK/STAT, MAPK and PI3K pathways. Some IL-21 target genes, such as B lymphocyte induced maturation protein-1 (Blimp-1), suppressor of cytokine signaling (SOCS), CXCR5 and Bcl-6, play important roles in the immune response. Therefore, IL-21 has been linked to autoimmune diseases. Indeed, IL-21 levels are increased in the peripheral blood and tissues of patients with systematic lupus erythematosus (SLE), rheumatoid arthritis (RA), type 1 diabetes (T1D), immune thrombocytopenia (ITP), primary Sjogren's syndrome (pSS), autoimmune thyroid disease (AITD) and psoriasis. This increased IL-21 even positively associates with Tfh cells, plasma cells, autoantibodies and disease activity in SLE and RA. Additionally, IL-21 has been utilized as a therapeutic target in SLE, RA, T1D and psoriatic mouse models. Profoundly, clinical trials have shown safety and improvement in RA patients. However, tolerance and long-term pharmacodynamics effects with low bioavailability have been found in SLE patients. Therefore, this review aims to summarize the latest progress on IL-21 function and its signaling pathway and discuss the role of IL-21 in the pathogenesis of and therapy for autoimmune diseases, with the hope of providing potential therapeutic and diagnostic strategies for clinical use. Highlights: IL-21 levels are increased in the peripheral blood and tissues of autoimmune patients. IL-21 has been utilized as a therapeutic target in SLE, RA, T1D and psoriatic mouse models. Clinical trials have shown safety and improvement in RA patients. IL-21 promotes B cell maturation and function mainly mediated by activation of the JAK/STAT, MAPK and PI3K pathways.